Sosialisasi Pentingnya Peran Teknologi Digitalisasi Dalam Pengembangan Usaha Pengrajin Gamelan UD Kayu Mas di Kelurahan Dangin Puri Denpasar Timur - Desak Gde Dwi Arini; Ni Gusti Ketut Sri Astiti; Nengah Ganawati (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2024)
One of the gamelan craftsmen in Dangin Puri Village, specifically UD Kayu Mas, lacks basic knowledge or skills in digital technology. Considering the importance of digital technology in business development, it is necessary to conduct socialization and training to enhance the understanding and skills of UD Kayu Mas gamelan craftsmen in utilizing digital technology for their business growth. The socialization involves explaining the importance of digitalization in expanding markets and growing businesses, such as creating and using online platforms to sell products, and teaching how to leverage social media for promotion, including Instagram, Facebook, and online marketplaces for product marketing. In addition, KKN students help create an online business profile and promotional video for UD Kayu Mas gamelan craftsmen. The output from the KKN activities includes a survey conducted at UD Kayu Mas to obtain approval and confirm the schedule from the business owner to carry out socialization about the importance of digitalization in business development for the gamelan craftsmen. This is expected to ensure that the socialization activities run smoothly and benefit UD Kayu Mas as the target for education and socialization. The craftsmen are expected to have a better understanding of digitalization and be able to apply it in their businesses. They can expand their business networks through digital platforms, which is expected to lead to increased sales and operational efficiency. Meanwhile, the publication outputs include a Community Service Journal and KKN-PPM report, along with a YouTube link.